Application of Problem-Based Learning in Improving Student Learning Outcomes in Islamic Education Learning at SD IT Robbani Ujung Batu 1 - Elinda, Melvi; Maulida; Hasibuan, Baktiar (MANDAILING GLOBAL EDUKASIA, 2024)
This research aims to improve student learning outcomes in the subject of Islamic Religious Education Asmaul Husna material by applying problelm-based learning can improve student learning outcomes in learning Islamic religious education material Teladan Mulia Asmaul Husna class IV A at SD IT Robbani Ujung Batu 1 Academic Year 2024/2025. The background of this study is the low learning outcomes of students caused by the use of less varied learning methods, such as lectures, which make students passive and unmotivated to learn. This study uses the Classroom Action Research method which is carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The subjects of the study were 24 grade 4 students of SD IT Robbani Ujung Batu 1. Data were collected through observations, interviews, and learning outcome tests. The results of the study showed a significant increase in student learning outcomes. in the first cycle, a score of 58.33 % was obtained. in the second cycle, a score of 87.5% was obtained. The application of Problelm-Based Learning has been proven to increase students' active participation in group discussions and increase their understanding of Asmaul Husna's material. Based on the results of the study, it was concluded that the Problelm-Based Learning model is effective in improving learning outcomes and student participation. It is recommended that this learning model continues to be applied with a variety of more interactive methods to improve the quality of learning.